2015
DOI: 10.1246/cl.150704
|View full text |Cite
|
Sign up to set email alerts
|

π-Expanded Axially Chiral Biaryls and Their Emissions: Molecular Design, Syntheses, Optical Resolution, Absolute Configuration, and Circularly Polarized Luminescence of 1,1′-Bipyrene-2,2′-diols

Abstract: Axially chiral biaryls based on pyrene, 1,1¤-bipyrene-2,2¤-diol derivatives 2, were designed and synthesized from 2-hydroxypyrene. Simple optical resolution was carried out and the absolute configuration was determined by diffraction study. Title compounds 2 and corresponding menthylcarbonate 4 showed clear circularly polarized luminescence (CPL) spectra. The degree of dimensionless Kuhn's anisotropy in the photoexcited state («g em «) of 2 and 4 were ca. 3.6 © 10 ¹4 and ca. 1.2 © 10 ¹3, respectively. Notewort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 24 publications
1
33
0
1
Order By: Relevance
“…The dihedral angle between the two central naphthyl moieties can be altered by chemical modification of the central region; for example, acid‐catalyzed dehydration involving the central OH groups delivers an additional furan system, which in turn decreases the dihedral angle from 86.4° to 14.6°, as predicted by DFT methods. The protected 1,1′‐bi‐2‐pyrenol ( 12 , Figure ) can be prepared by the Fe III ‐ or Cu II ‐mediated oxidative dimerization of the protected precursor of 2‐pyrenol. After dimerization, diastereomers of type 12 can be effectively separated using conventional chromatography and then be deprotected to deliver optically pure 1,1′‐bi‐2‐pyrenols.…”
Section: Intermolecular Oxidative Aromatic Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The dihedral angle between the two central naphthyl moieties can be altered by chemical modification of the central region; for example, acid‐catalyzed dehydration involving the central OH groups delivers an additional furan system, which in turn decreases the dihedral angle from 86.4° to 14.6°, as predicted by DFT methods. The protected 1,1′‐bi‐2‐pyrenol ( 12 , Figure ) can be prepared by the Fe III ‐ or Cu II ‐mediated oxidative dimerization of the protected precursor of 2‐pyrenol. After dimerization, diastereomers of type 12 can be effectively separated using conventional chromatography and then be deprotected to deliver optically pure 1,1′‐bi‐2‐pyrenols.…”
Section: Intermolecular Oxidative Aromatic Couplingmentioning
confidence: 99%
“…[21] Theo xidative dimerization of larger phenols represents one of the most convenient pathways toward complex 2,2'dihydroxybiaryl compounds.According to the Tsubaki group, butterfly-shaped molecule 11 can be obtained by the Cu IImediated dimerization of dinaphthofuran-6-ol ( Figure 2). [22] Thedihedral angle between the two central naphthyl moieties can be altered by chemical modification of the central region; for example,acid-catalyzed dehydration involving the central OH groups delivers an additional furan system, which in turn decreases the dihedral angle from 86.48 8 to 14.68 8,aspredicted by DFT methods.T he protected 1,1'-bi-2-pyrenol (12, Figure 2) can be prepared by the Fe III - [23] or Cu II -mediated [24] oxidative dimerization of the protected precursor of 2pyrenol. After dimerization, diastereomers of type 12 can Structures of newly designed Mo-based mediators for oxidative coupling.…”
Section: Oxidative Homocoupling Of Arenes and Heteroarenesmentioning
confidence: 99%
“…Pyrene is a typical π‐expanded PAH that is characterized by its photophysical property and relatively high‐lying HOMO energy level . Utilizing these properties, many pyrene‐based advanced materials have been synthesized, and our research group has contributed to this research field through the synthesis of structurally well‐defined oligopyrenylene, a pyrene‐based PAH, and pyrene dimers emitting circularly polarized luminescence . In this study, we designed pyrene‐substituted quinones 1 a and 2 a .…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that 1,1′‐bi‐2‐naphthol [( R )‐ 3 ] and 2,2′‐diethoxy‐1,1′‐binaphthyl [( R )‐ 6 ], commonly exhibit a negative CPL signal in the weakly‐polar chloroform (CHCl 3 ) . In this work, ( R )‐ 3 and ( R )‐ 6 both exhibited a negative CPL signal in the highly polar dimethylformamide (DMF) (Figures (b) and (b); black dotted line).…”
Section: Resultsmentioning
confidence: 62%